NLRP-3 Expression in Pancreatic Tissue Following Moderate and High Intensity Interval Training with Liposomal Alpha-Lipoic Acid Supplement in Diabetic Rats - Seyed Abdollah Fatemi; Amin Frzaneh Hesari; Minoo Dadban shahamat (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2022)
Introduction: Activation of NLRP-3 Inflammasome is considered an indicator of chronic inflammation in type 2 diabetes. Regular exercise training along with antioxidants supplements can control inflammation. The aim of the present study was to investigate the effect of training with different intensity and alpha lipoic acid supplement on pancreatic NLRP-3 expression in diabetic rats. Methods: In this experimental study, 35 Wistar rats were randomly divided into seven groups: control, diabetic, diabetic+ supplement (S), diabetic+ high intensity training (HIT), diabetic+ moderate intensity training (MIT), diabetic+ high intensity training + supplementation (HIT+S), diabetic+ moderate intensity training + supplementation (MIT+S). The HIT and MIT protocols were performed five days a week for six weeks. HIIT included 10 bouts of four minutes running (at 85–90% of VO2max) and MIT, 13 bouts of four minutes running (at 65–70% of VO2max). Alpha lipoic acid was administered orally at a dose of 20 mg/kg was given to rats once a day by gavage. Blood and tissue sample was taken 24 h after last exercise session. Real-time PCR method for the relative expression of NLRP-3 gene expression was used. Results: Expression of LRP-3 gene in pancreatic tissue was increased significantly in the diabetic group compared to control group (p=0.0001). In addition, S (P = 0.021), MIT (P = 0.009), HIT (P = 0.001), MIT+S (P = 0.003) and HIT+S (P = 0.0001), significantly reduced the NLRP-3 levels in pancreatic tissue compared to the diabetic group. Conclusion: Type 2 diabetes is associated with increased mRNA NLRP-3 in pancreatic tissue. MIT and HIT plus alpha lipoic acid can be considered as an effective intervention in decreasing pancreatic mRNA NLRP-3 in diabetic rats.